Analisis Faktor Penyebab Perilaku Penyalahgunaan Narkoba Ditinjau dari Perspektif Islam dan Kesehatan Masyarakat: Literatur review - Faiz, Jihan Fadilah; Alkaff, Raihana Nadra; Muntahaya, Fika; Wiza, Siti Salmah; Gunawan, Dio; Fauziah, Amelia Lutfi; Ramadhani, Asri; Rohmah, Khofifah (Journal of Religion and Public Health, 2023)
AbstractDrug abuse is a public health problem that still occurs in Indonesia. This problem is not limited to certain age groups. Starting from the adult age group, adolescence to the age group of children who know and use drugs. This paper aims to analyze the factors that cause drug’s abuse behavior using Precede-Proceed theory approach from an Islamic and public health perspective. This study is a narrative literature review using the keywords